Microbiological Quality of Irrigation Water and Leafy Vegetables in Dar es Salaam, Tanzania - Kamara, Bubelwa L.; Mrema, Godwill D.; Lyimo, Thomas J. (Tanzania Journal of Science, 2024)
The quality of water used for the irrigation of leafy vegetables in urban settings is in doubt due to contamination associated with poor hygiene and water pollution. This study examined the microbiological quality of irrigation water and leafy vegetables at Chang’ombe in Dar es Salaam, Tanzania as well as the perceptions and level of awareness of nearby consumers. Water and leafy vegetable samples were analysed for faecal coliform (FC) using standard techniques. Perception and awareness of consumers were collected using a questionnaire survey. The results showed an average FC count of 406.1 ± 16.40 MPN/100 ml for the irrigation water. The sweet potato leaves and amaranth had FC counts of 11.40 ± 5.220 CFU/g and 17.60 ± 11.98 CFU/g respectively. The levels of FC in irrigation water and leafy vegetables were within the allowed limits by WHO and NAS-USA standards respectively but fall short of some stricter European standards for irrigation water. The household survey showed that consumers perceive irrigation water at Chang’ombe as polluted and may be one of the main sources of food contamination. They minimize associated health risks in various ways such as using clean storage, washing and cooking. It was concluded that the microbial quality of water used for irrigation of leafy vegetables at Chang’ombe poses no risk to public health, but based on tighter standards, improved public awareness of hygienic practices is crucial to address potential risks.